(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We are currently doing import substitution in line with the ’Swadeshi philosophy.’ In truth, we have been exercising import substitution. In our nation there was a low wage, a low expenditure savings rate, an ongoing debt, a highly low development rate. Apart from this attractive growth rate for Asian tigers, then the IMF strategy, our policymakers were forced to liberalize and globalize with many other events. A major shift was made from a sleeping policy to an open-ended one. The present article is of its nature in India that seeks to encourage evidence of the impact on the Indian economy, measured under a time varying parameter regression model, of inward foreign investments at macro level as well as at the basic three-sector level. The study documents significantly differing findings in various sectors of the economy through a sector-level analysis. The study suggests that policymakers rejuvenate India’s primary sector to draw and consume more intra-DFIs and ensure sustainable economic growth. The study results indicated that liberalization has positive impact on service sector growth while a negative impact on manufacturing sector growth. In conclusion the study shows a sectoral imbalance in India.